Upaya Sekolah dalam Mencegah Praktik Korupsi di Dunia Pendidikan - Zainudin Hasan; Daniel Junesco (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Corruption is a serious issue that hinders development and disrupts the social order in Indonesia. Efforts to prevent corruption rely not only on law enforcement but also on character building and the instillation of integrity from an early age. Education in schools plays a crucial role in shaping young generations with integrity and an awareness of anti-corruption values. Through a curriculum that emphasizes moral values, ethics, and social responsibility, schools can serve as the foundation for creating a society free from corruption. Anti-corruption education must become an integral part of the national education system. As a recommendation, the government and relevant stakeholders should strengthen the implementation of anti-corruption education in schools by providing teacher training and developing age-appropriate materials for students. The suggestion needed is to provide training to security guards and canteen guards, so that students get better anti-corruption education.